Fifth Five Year Plan Proposal Vol. 5. Government of Tripura - Planning Commission (Planning Commission, 1973)
Outlay and Expenditure Summary, Outlays for Backward Areas Programme wise Outlay and Expenditure Physical Programmes Targets and Achievements Minimum Needs Programme Outlay and Expenditure Minimum Needs Programme Physical Targets Sectoral Statements.
Government of Tripura Planning and Coordination Department
Government of Tripura Planning and Coordination Department